Effect of Annurca Apple Polyphenols on Intermittent Claudication in Patients With Peripheral Artery Disease - Tenore, Gian Carlo; D'Avino, Maria; Caruso, Domenico; Buonomo, Giuseppe; Acampora, Ciro; Caruso, Giuseppe; Simone, Crescenzo; Ciampaglia, Roberto; Novellino, Ettore (The American journal of cardiology, 2019)
Peripheral arterial disease (PAD) is an atherosclerotic process involving both modifiable and nonmodifiable risk factors. Prospective cohort studies show that patients with PAD have a 6-fold greater risk of death from cardiovascular disease than those without PAD. Currently, there is no effective treatment for PAD. The study was a randomized, placebo-controlled trial, involving 180 patients, aged 35 to 75. The subjects were divided into 2 groups. One group underwent 24 weeks of nutraceutical treatment consisting in the administration of 4 capsules of Annurca apple polyphenolic extract (AMS)/day. The placebo group was administered with identically appearing capsules containing only maltodextrin. Primary outcome measures were: walking autonomy, ankle-brachial index, acceleration time. In the AMS group, at the end of the treatment period, walking autonomy was increased on average by 69% (p <0.05), while slighter effects were registered as regards ankle-brachial index (+25%; p <0.05) and acceleration time (−3.6%; p <0.05), when compared with baseline. Placebo group revealed no significant differences as regards variations of all outcomes measures (p >0.05). Our preliminary results may indicate AMS product as a promising natural and safe tool for treatment of symptoms related to PAD.